SOME ASPECTS OF AMENDING AND CANCELING AN ADMINISTRATIVE DOCUMENT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The experience of foreign countries has shown that there are various methods for changing, canceling and invalidating an administrative document and that they are being effectively used. The clear definition of these mechanisms allows for the resolution of such disputes through a single procedure. This prevents unnecessary expenditure of time and money by citizens, and also saves state resources.